THE INFLUENCE OF TIMING AND AGE ON HASSLE REGULATION EFFICACY. (11th November 2018) - Bellingtier, J A; Luong, G; Riediger, M
Abstract: Building on the Strength and Vulnerability Integration (SAVI) model (Charles, 2010), which suggests age-related differences in reactivity will emerge once sufficient time has passed for older adults to capitalize on their emotion regulation strengths, recent research has sought to clarify previous mixed findings regarding age-related differences in stressor reactivity, with findings affirming the importance of stressor timing (Scott et al., 2014; Wrzus et al., 2014). Using an experience sampling approach, this study sought to examine age-related differences in post-stressor negative affect when various emotion regulation strategies are implemented (e.g., positive reappraisal, social sharing, etc.). Participants ranged in age from 14 to 99 (n = 367, Mage = 44, 46% men) and were prompted to report their stressors, regulation strategy use, and affect 6 times a day on at least 9 days over a 3-week period. Results suggest age-related differences in negative affect vary based on regulation strategy and stressor timing.